2014
DOI: 10.9790/1684-11433844
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterisation of Aluminium Alloy - Bagasse Ash Composites

Abstract: The study was carried out to determine the density and mechanical properties of Al-7%Si alloy-Bagasse Ash (BA) composite produced at 800 o C. BA obtained at 700 o C and having high silica and alumina contents of up to 77.29% and 10.95%, respectively was used as reinforcement and varied from 0vol% to 30vol%. The density and some mechanical properties of the produced composites were determined. The results showed that the density decreases with percentage increase in reinforcement from 2840.242kgm-3 to 2292.208k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…1. A decrease in the density of Al-7%Si-bagasse ash composite with the increased percentage of reinforcement was also recorded by Usman et al [21]. The best result of decrease in the density was obtained at 30 vol.% of bagasse ash by the same author.…”
Section: Physical Properties Of Monolithic Compositessupporting
confidence: 57%
See 2 more Smart Citations
“…1. A decrease in the density of Al-7%Si-bagasse ash composite with the increased percentage of reinforcement was also recorded by Usman et al [21]. The best result of decrease in the density was obtained at 30 vol.% of bagasse ash by the same author.…”
Section: Physical Properties Of Monolithic Compositessupporting
confidence: 57%
“…Studies [13,16,19,21,32,34,40,42] [13]. An improvement in the compressive strength of the composites developed by modified compo-casting followed by squeeze casting has been observed.…”
Section: Mechanical Properties Of Monolithic Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum alloy has vast engineering applications particularly in space industries, automobiles, marine components, sports equipment, and household utensils (Sunil, Keshavamurthy, Prakash, and Channabasappa, 2015). Bagasse ash composed mostly of oxides of silicon (SiO2), iron (Fe2O3), aluminum (Al2O3), and others as detailed by (Usman, Raji, Waziri, and Hassan, 2014). Bagasse used as reinforcement has provided an alternative for synthetic reinforcement like alumina (Al2O3) and silicon carbide (SiC), and widely available and cheap (Singh, Kumar, Kumar, Maurya, and Dwivedi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A. Baradeswaran et al [5] Studied on mechanical and tribological behavior of Aluminium 7075 hybrid composites with 2-8 percentages by weight of Al2O3 particles and 5 percent by weight of graphite and found that hardness and tensile strength of composites increased with increasing Al2O3 content. Some works have been carried out to study the characterization of Al 7075 MMC [6]. The various specimens of the composite with varying weight percentages of reinforced material were made and experiments were conducted using L9 orthogonal array and the properties of the composite and their significant changes were evaluated [7].…”
Section: Introductionmentioning
confidence: 99%